Annotation as a Tool of Multimodal Analysis: From Text to Meaning - Krysanova, Tetiana (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
The article focuses on the role of annotation as an effective tool for meaning-making in multimodal texts. The relevance of annotations lies in their ability to capture all aspects of semiotic interaction, integrate semiotic resources beyond linguistic elements, and reveal generalized patterns of communication. The objective of this study is to identify the characteristics of annotating environmental videos produced by Greenpeace aiming to determine the content aspects of multimodal constructions related to climatic change. The research methods are based on Grounded Theory, emphasizing data coding and categorization to uncover key themes and patterns in the meaning-making process. The annotation methodology is based on the principles of selectivity, sequentiality, segmentation, and systematicity, encompassing several stages: data collection, transcription, coding, and interpretation. Initial coding led to the identification of various codes, which subsequently formed three key categories. The first category, EMOTIONAL AND SENSORY IMPACT, includes codes that stimulate emotional responses and sensory engagement from the audience. The second category, ENVIRONMENTAL THREAT, encompasses codes illustrating various aspects of environmental threats, including their causes, effects on the environment, and potential victims. The third category, ENVIRONMENTAL ACTIONS AND RESPONSES, consists of codes that represent possible approaches to counter climate change. The integration of these categories yields a central category—ENVIRONMENTAL AWARENESS THROUGH EMOTIONAL AND SENSORY EXPERIENCE, which encapsulates the multifaceted impact of environmental issues. This suggests that the interplay of emotions, threats, and actions is fundamental to the meaning-making process in videos created by Greenpeace.